The Development of Methods of BLOTCHIP®-MS for Peptidome: Small Samples in Tuberous Sclerosis - Kunio Yui; George Imataka; Kotaro Yuge; Hitomi Sasaki; Tadashi Shiohama; Kyoichi Asada; Hidehisa Tachiki (Current Issues in Molecular Biology)
Mutations in TSC1 or TSC2 in axons induce tuberous sclerosis complex. Neurological manifestations mainly include epilepsy and autism spectrum disorder (ASD). ASD is the presenting symptom (25–50% of patients). ASD was observed at significantly higher frequencies in participants with TSC2 than those with TSC1 mutations. The occurrence of TSC2 mutations is about 50% larger than TSC1. Therefore, ASD may develop due to TSC2 deficiency. TSC2 regulates microRNA biogenesis and Microprocessor activity via GSK3β. Of reference, everolimus has the best treatment target because of the higher potency of interactions with mTORC2 rather than rapamycin. Mutations in the TSC1 and TSC2 genes result in the constitutive hyperactivation of the mammalian target of the rapamycin (mTOR) pathway, contributing to the growth of benign tumors or hamartomas in various organs. TSC2 mutations were associated with a more severe phenotypic spectrum than TSC1 mutations because of the inhibition of the mTOR cascade. There are few studies on the peptide analysis of this disorder in relation to everolimus. Only one study reported that, in ten plasma samples, pre-melanosome protein (PMEL) and S-adenosylmethionine (SAM) were significantly changed as diagnostic prognostic effects. Our study on peptide analysis in Protosera Inc (Osaka, Japan) revealed that three peptides that were related to inflammation in two patients with tuberous sclerosis, who showed a 30% decrease in ASD symptoms following everolimus treatment. TSC2 mutations were associated with a more severe phenotypic spectrum due to the inhibition of the mTOR cascade. PMEL and SAM were significantly changed as diagnostic effects.